PENGEMBANGAN MEDIA PEMBELAJARAN BERBANTUAN PERMAINAN KARTU UNO UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR PESERTA DIDIK SMA - Febriani, Yuliana (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2024)
The objectives of this study are: (1) to produce UNO card media that is feasible to increase students' interest and learning outcomes; (2) to produce UNO card media that is practical to increase students' interest and learning outcomes; (3) to produce UNO card media that is effective to increase students' interest and learning outcomes. The research design used is RD with the 4D model (define, design, develop, disseminate). The research subjects were students of class XI SMA Negeri 1 Pengasih. Data collection techniques include interviews, observations, questionnaires, and tests. analysis techniques using four-scale ideal standard deviation (SBi) techniques, Aiken's V, IJA, Quest Standard Gain, Mann Whitney, Effect Size. The results showed that the UNO card game media was feasible, practical and effective to increase the interest and learning outcomes of grade XI students.